Perception Of Ethical Phenomena in Marketing Communication in The Digital Space Within the Slovak Republic: A Qualitative Research - Tatiana COREJOVA; Barbora MISIKOVA; Maria ROSTASOVA; Alexandra VALICOVA (Communications of International Proceedings, 2022)
Due to the use of new technologies, there are changes in the business model of individual companies as well as in the electronic support of marketing tools. The constant development of technology and innovation can raise customers' concerns about digital monitoring or loss of privacy, as well as indicate various unethical and dangerous phenomena in relation to the consumer. The aim of the paper is to point out unethical phenomena in the advertising industry and in marketing communication in the digital space within the Slovak Republic. In terms of the ethical dimensions of consumer protection, an information gap has been noted regarding unethical phenomena in advertising. The results of the quantitative survey pointed to breaches of advertising ethics by advertisers, in particular in terms of truthfulness, decency and general advertising requirements. The information gap was filled by primary research, carried out by electronic interrogation. The primary research showed that it was identified in 2021 compared to 2020 higher percentage of unethical phenomena on the Internet among respondents, e.g. 87% compared to 64%, while 76.9% of respondents perceive the violation of ethical behaviour in the field of decency of advertising and 75.5% of respondents are hindered by unethical behaviour in advertising, but only 9.7% of respondents are willing to take the necessary steps against it.
Keywords: Business model; online communication; marketing ethics